2022
DOI: 10.3390/plants11091161
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gamma Radiation for the Genetic Improvement of Underutilized Plant Varieties

Abstract: Agricultural biodiversity includes many species that have biological variants (natives, ecotypes, races, morphotypes). Their use is restricted to local areas because they do not fulfill the commercial requirements; however, it is well documented that these species are a source of metabolites, proteins, enzymes, and genes. Rescuing and harnessing them through traditional genetic breeding is time-consuming and expensive. Inducing mutagenesis may be a short-time option for its genetic improvement. A review of out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 56 publications
0
22
0
2
Order By: Relevance
“…For example, 50 Gy gamma radiation produced a sensitizing effect on chloroplasts. Moreover, high Gy doses affect protein synthesis, hormonal balance, enzymatic activity, gas, and water exchange (Riviello-Flores et al, 2022). Nowadays, new variations are needed to develop more nutritious, resistant, and productive varieties (Amri-Tiliouine et al, 2018;Shuryak et al, 2019).…”
Section: Gamma Radiation In Plant Breedingmentioning
confidence: 99%
“…For example, 50 Gy gamma radiation produced a sensitizing effect on chloroplasts. Moreover, high Gy doses affect protein synthesis, hormonal balance, enzymatic activity, gas, and water exchange (Riviello-Flores et al, 2022). Nowadays, new variations are needed to develop more nutritious, resistant, and productive varieties (Amri-Tiliouine et al, 2018;Shuryak et al, 2019).…”
Section: Gamma Radiation In Plant Breedingmentioning
confidence: 99%
“…The number of seeds tip, and leaf shape. The variables of leaf morphology in this study were based on observations during the research and several studies related to changes in leaf shape due to irradiation treatment (Meilawati et al 2016;Riviello-Flores 2022). As for leaf color, the percentage of each color is calculated based on observations during the research.…”
Section: Accelerated Aging and Gamma Irradiation Treatmentsmentioning
confidence: 99%
“…These parameters depend on the dosage, species, varieties, plant tissue (seed, meristem, callus, etc. ), stage of development, and moisture content in the radiation time (Riviello-Flores et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors so far reported a reduction of regenerative capacity and malformation of plant tissues, as well as, tissue destruction due to the high dose of radiation (Chakravarty and Sen, 2001;Yamaguchi, 2018;Andrew-Peter-Leon et al, 2021). Radio sensitivity tests are essential for determining the appropriate radiation dose to induce the highest genetic diversity with the most useful fixed mutations (Songsri et al, 2019;Riviello-Flores et al, 2022). Studies also stated that irradiation with low radiation doses stimulates the plants' vitality, which is beneficial for plant regeneration (Jala and Bodhipadma, 2011;Abubakar et al, 2017;Surakshitha and Soorianathasundaram, 2017;Aisyah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%